EVALUACIÓN POR MÉTODO ECOMÉTRICO DE AGAR OBTENIDO DE ALGAS ROJAS COLOMBIANAS - A. Villalobos; L. Calderón; C. Figueroa; J. Fierro; G. Otalóra; B. Quevedo-Hidalgo; R. Álvarez; M. Mercado-Reyes; M. Huertas-Valero; A. Trespalacios-Rangel (Universitas Scientiarum)
The purpose of this study was to evaluate the productivity on agar-agar of two species of red algae of thegenera Gracilaria belonging from the Colombiam Caribean coast (G. cylindrica and G. mammillaris)obtained in laboratory. Productivity of culture media elaborated with base agar - agar was determinedusing the ecometric method with 20 different bacterial species. Results obtained from ICA and ICRshowed that agar extracted from Gracilaria cylindrica and Gracillaria mammillaris are equally productive,this shows that both species can be used for agar production. For better results, it is still necessary tooptimize extraction processes and purification of agar in both species of algae.